Genomics-inspired discovery of massiliachelin, an agrochelin epimer from Massilia sp. NR 4-1 - Diettrich, Jan; Kage, Hirokazu; Nett, Markus (Beilstein Journal of Organic Chemistry, 2019)
A putative siderophore locus was detected in the genome of the violacein-producing bacterium Massilia sp. NR 4-1 and predicted to direct the biosynthesis of a molecule that is structurally related to the thiazoline-containing siderophore micacocidin. In order to track this compound, we analyzed the metabolic profiles of Massilia cultures grown under different iron concentrations. A compound which was found to be predominantly produced under iron deficiency was subsequently isolated. Its structural characterization by spectroscopic and bioinformatic analyses revealed a previously not known diastereomer of the cytotoxic alkaloid agrochelin. The structure of this natural product, which was named massiliachelin, corresponds to the assembly line encoded by the identified siderophore locus.
Keywords: agrochelin; genome mining; Massilia; massiliachelin; siderophore; stereochemistry

(untitled) - Masschelein, J.; Jenner, M.; Challis, G. L. (Nat. Prod. Rep., 2017)

(untitled) - Challinor, V. L.; Bode, H. B. (Ann. N. Y. Acad. Sci., 2015)

(untitled) - Molloy, E. M.; Hertweck, C. (Curr. Opin. Microbiol., 2017)

(untitled) - Ling, L. L.; Schneider, T.; Peoples, A. J.; Spoering, A. L.; Engels, I.; Conlon, B. P.; Mueller, A.; Schäberle, T. F.; Hughes, D. E.; Epstein, S.; Jones, M.; Lazarides, L.; et al. (Nature, 2015)

(untitled) - Lincke, T.; Behnken, S.; Ishida, K.; Roth, M.; Hertweck, C. (Angew. Chem., Int. Ed., 2010)

(untitled) - Myeong, N. R.; Seong, H. J.; Kim, H.-J.; Sul, W. J. (J. Biotechnol., 2016)

(untitled) - Bode, H. B.; Bethe, B.; Höfs, R.; Zeeck, A. (ChemBioChem, 2002)

(untitled) - Graupner, K.; Scherlach, K.; Bretschneider, T.; Lackner, G.; Roth, M.; Gross, H.; Hertweck, C. (Angew. Chem., Int. Ed., 2012)

(untitled) - Fritsche, K.; van den Berg, M.; de Boer, W.; van Beek, T. A.; Raaijmakers, J. M.; van Veen, J. A.; Leveau, J. H. J. (Environ. Microbiol., 2014)

(untitled) - Kai, K.; Sogame, M.; Sakurai, F.; Nasu, N.; Fujita, M. (Org. Lett., 2018)

(untitled) - Blin, K.; Pascal Andreu, V.; de los Santos, E. L. C.; Del Carratore, F.; Lee, S. Y.; Medema, M. H.; Weber, T. (Nucleic Acids Res., 2019)

(untitled) - Blin, K.; Wolf, T.; Chevrette, M. G.; Lu, X.; Schwalen, C. J.; Kautsar, S. A.; Suarez Duran, H. G.; de los Santos, E. L. C.; Kim, H. U.; Nave, M.; Dickschat, J. S.; Mitchell, D. A.; et al. (Nucleic Acids Res., 2017)

(untitled) - Kreutzer, M. F.; Kage, H.; Gebhardt, P.; Wackler, B.; Saluz, H. P.; Hoffmeister, D.; Nett, M. (Appl. Environ. Microbiol., 2011)

(untitled) - Kage, H.; Kreutzer, M. F.; Wackler, B.; Hoffmeister, D.; Nett, M. (Chem. Biol., 2013)

(untitled) - Kreutzer, M. F.; Nett, M. (Org. Biomol. Chem., 2012)

(untitled) - Miller, D. A.; Luo, L.; Hillson, N.; Keating, T. A.; Walsh, C. T. (Chem. Biol., 2002)

(untitled) - Souto, A.; Montaos, M. A.; Rivas, A. J.; Balado, M.; Osorio, C. R.; Rodríguez, J.; Lemos, M. L.; Jiménez, C. (Eur. J. Org. Chem., 2012)

(untitled) - Cañedo, L. M.; de la Fuente, J. A.; Gesto, C.; Ferreiro, M. J.; Jiménez, C.; Riguera, R. (Tetrahedron Lett., 1999)

(untitled) - Ankenbauer, R. G.; Cox, C. D. (J. Bacteriol., 1988)

(untitled) - Rinehart, K. L.; Staley, A. L.; Wilson, S. R.; Ankenbauer, R. G.; Cox, C. D. (J. Org. Chem., 1995)

(untitled) - Schlegel, K.; Taraz, K.; Budzikiewicz, H. (BioMetals, 2004)

(untitled) - Drechsel, H.; Stephan, H.; Lotz, R.; Haag, H.; Zähner, H.; Hantke, K.; Jung, G. (Liebigs Ann., 1995)

(untitled) - Patel, H. M.; Tao, J.; Walsh, C. T. (Biochemistry, 2003)

(untitled) - Youard, Z. A.; Mislin, G. L. A.; Majcherczyk, P. A.; Schalk, I. J.; Reimmann, C. (J. Biol. Chem., 2007)

(untitled) - Kobayashi, S.; Nakai, H.; Ikenishi, Y.; Sun, W.-Y.; Ozaki, M.; Hayase, Y.; Takeda, R. (J. Antibiot., 1998)

(untitled) - Ino, A.; Hasegawa, Y.; Murabayashi, A. (Tetrahedron, 1999)

(untitled) - Ino, A.; Murabayashi, A. (Tetrahedron, 2001)

(untitled) - Miller, M. C.; Parkin, S.; Fetherston, J. D.; Perry, R. D.; DeMoll, E. (J. Inorg. Biochem., 2006)

(untitled) - Caffrey, P. (ChemBioChem, 2003)